2010
DOI: 10.1111/j.1471-0528.2010.02777.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative peritoneal immune profiles, T-cell apoptosis and oxidative stress-associated characteristics in women with minimal and mild endometriosis

Abstract: Please cite this paper as: Mier‐Cabrera J, Jiménez‐Zamudio L, García‐Latorre E, Cruz‐Orozco O, Hernández‐Guerrero C. Quantitative and qualitative peritoneal immune profiles, T‐cell apoptosis and oxidative stress‐associated characteristics in women with minimal and mild endometriosis. BJOG 2011;118:6–16. Objectives  To assess immunological variables, T‐cell apoptosis and oxidative stress markers in the peripheral blood and peritoneal fluid of women with (WEN) and without (WWE) endometriosis. Design  Observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 37 publications
6
74
0
3
Order By: Relevance
“…Altered immune responses play a prominent role in the development of peritoneal endometriosis due to failure to remove the ectopic endometrial cells (Giudice & Kao 2004, Mier-Cabrera et al 2010. Numerous evidences indicate that the immune cells facilitate the establishment of endometriotic lesion and modulate endometriosis-associated pain and infertility as well (Berbic et al 2009).…”
Section: Iron-induced Peritoneal Os In Endometriosis Developmentmentioning
confidence: 99%
“…Altered immune responses play a prominent role in the development of peritoneal endometriosis due to failure to remove the ectopic endometrial cells (Giudice & Kao 2004, Mier-Cabrera et al 2010. Numerous evidences indicate that the immune cells facilitate the establishment of endometriotic lesion and modulate endometriosis-associated pain and infertility as well (Berbic et al 2009).…”
Section: Iron-induced Peritoneal Os In Endometriosis Developmentmentioning
confidence: 99%
“…Up to day numerous papers reported increased levels of different oxidative stress markers in peritoneal fluid of endometriosis cases. 8,12,13,21 The results of this study suggested that OS, detected as elevated IMA levels, may be confined to the peritoneal cavity in women with advanced stage endometriosis. Moreover, this is the first is study in the literature documenting IMA levels in peritoneal fluid of endometriosis cases.…”
Section: Discussionmentioning
confidence: 84%
“…In endometriosis, peritoneal fluid contains high concentrations of pro-inflammatory and chemotactic cytokines that activates phagocytic cells and apoptotic endometrial tissue accumulated in endometriotic implants, which are the basic producers of ROS. 12 Therefore, in our study peritoneal fluid IMA levels were analysed as well. Up to day numerous papers reported increased levels of different oxidative stress markers in peritoneal fluid of endometriosis cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several independent studies regarding this pathology and oxidative stress biomarkers, peritoneal fluid from women suffering from endometriosis was found to have increased levels of MDA, 8-OHdG, 8-oxoguanine DNA glycosylase, protein carbonyls, interleukin-6, TNFα, interleukin-1β, interleukin-8, VEGF, and 8-iso-prostangladin F2-alpha (8-iso-PGF2α) (Andrade et al2010;Carvalho et al 2013;Matsuzaki and Schubert2010;Mier-Cabrera et al 2011;Montuschi et al 2004;Morrow et al 1992;Rong et al 2002;Sharma et al2010). Furthermore, 8-iso-PGF2α levels were concluded to be useful in predicting oxidative status in diseases such as endometriosis (Montuschi et al 2004;Morrow et al 1992;Sharma et al 2010).…”
Section: Ros and Fertility-related Diseases Endometriosismentioning
confidence: 99%